2017
DOI: 10.1038/s41598-017-16642-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and growth of organs in living whole embryo and larval grafts in zebrafish

Abstract: Age-related systemic environments influence neurogenesis and organ regeneration of heterochronic parabiotic partners; however, the difficulty of manipulating small embryos prevents the effects of aged systemic environments on primitive organs at the developmental stage from being analysed. Here, we describe a novel transplantation system to support whole living embryos/larvae as grafts in immunodeficient zebrafish by the intrusion of host blood vessels into the grafts, allowing bodies similar to those of heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the present study, the embryonic pronephros of larval Florida pompano developed into the larval kidney during the first 7 dph. Mesonephric tubules and glomeruli increased in number, and interspersed hematopoietic islands Boglione et al, 1995;Crespo et al, 2001;Dias et al, 2022;Giménez & Estévez, 2008;Kawasaki et al, 2017;Koumoundouros et al, 2004;Nowak & Battaglene, 1996;Peruzzi et al, 2004;Sivaloganathan et al, 1996). The causes and effects of cystic calculi in these species remain unclear, but both environmental (salinity and temperature) and nutritional (dietary mineral and taurine) factors have been shown to play a role (Dias et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the embryonic pronephros of larval Florida pompano developed into the larval kidney during the first 7 dph. Mesonephric tubules and glomeruli increased in number, and interspersed hematopoietic islands Boglione et al, 1995;Crespo et al, 2001;Dias et al, 2022;Giménez & Estévez, 2008;Kawasaki et al, 2017;Koumoundouros et al, 2004;Nowak & Battaglene, 1996;Peruzzi et al, 2004;Sivaloganathan et al, 1996). The causes and effects of cystic calculi in these species remain unclear, but both environmental (salinity and temperature) and nutritional (dietary mineral and taurine) factors have been shown to play a role (Dias et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by ~96 hpf (3 dph) and 1 day after enriched rotifer feeding initiation, cystic calculi were visible in the early urinary bladder of many observed pompano larvae. Cystic calculi have been noted in other marine teleost larvae reared in aquaculture including sea bass, Dicentrarchus labrax , brown‐marbled grouper, Epinephelus fuscoguttatus , Japanese flounder, Paralichthys olivaceus , common dentex, Dentex dentex , gilthead sea bream, Sparus aurata , snapper, Pagrus auratus , mulloway, Argyrosomus hololepidotus , Australian bass, Macquaria novemaculeata , and striped trumpeter, Latris lineata (Allon et al, 2016; Boglione et al, 1995; Crespo et al, 2001; Dias et al, 2022; Giménez & Estévez, 2008; Kawasaki et al, 2017; Koumoundouros et al, 2004; Nowak & Battaglene, 1996; Peruzzi et al, 2004; Sivaloganathan et al, 1996). The causes and effects of cystic calculi in these species remain unclear, but both environmental (salinity and temperature) and nutritional (dietary mineral and taurine) factors have been shown to play a role (Dias et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed fin ray grafting using the rag1 line, a zebrafish mutant that lacks immune B and T cells, as a host (Figure 5a). Studies have shown that grafted testis and whole embryos are maintained for a long time using the rag1 mutant line (Kawasaki, Maeno, Shiroishi, & Sakai, 2017;Kawasaki, Siegfried, & Sakai, 2016). First, we tested the ability of fins to regenerate in the rag1 homozygous mutant line and observed that the rag1 mutant line normally regenerates the fin (Figure 5b), indicating that humoral immunity is not critical for normal fin regeneration.…”
Section: Non-epidermal Cells Specify Fin Lengthmentioning
confidence: 98%
“…Of the Poeciliids, G. holbrooki and G. affinis are the best examples of adaptation and survival under extreme environmental conditions [ 21 ] and are currently considered highly invasive species worldwide [ 22 ]. Such adaptive ability demands functional plasticity in organ development and their performance, with the heart the most critical for survival [ 23 ]. Studies in even the less hardy Poeciliids such as guppy, Poecilia reticulata , and Amazon molly, Poecilia formosa , have shown that they are less prone to heart diseases [ 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in embryonic zebrafish migration of primordial germ cells (PGCs) towards the putative gonadal ridge coincides with heart formation by 24 h post-fertilisation [ 35 ]. Moreover, a recent study indicated that there is a relation between primitive testis development with that of heart and liver in embryonic zebrafish [ 23 ], suggesting that many aspects of organogenesis are closely related and those obviously may thus bear witness to more cryptic sex differentiation events that occur in parallel.…”
Section: Introductionmentioning
confidence: 99%